TRAINING FUTURE TEACHERS PRESCHOOL PEDAGOGY AND PSYCHOLOGY TO INNOVATION PROFESSIONAL ACTIVITY: EXPERIMENTAL RESEARCH - Kozak, Liudmyla V. (Educological discourse, 2015)
The paper considers the steps and methods of organization of experimental work to validate the model and organizational-methodological foundations of training future teachers of pre-school pedagogy and psychology in innovative professional activity, analyzed and summarized the results of the pedagogical experiment.